Pembuatan The Hijau Dari Kulit Lidah Buaya (Aloe vera) Dengan Variasi Suhu Dan Lama Pengeringan - habib, Habib; suarti, Budi (Universitas Muhammadiyah Sumatera Utara, 2023)
One of the popular and very popular drinks is the tea. In addition to refreshing, tea has long been believed to provide many health benefits. Aloe vera plants have been widely cultivated and developed in Indonesia, in West Kalimantan Province, in Pontianak City on peatlands suitable for planting aloe vera. This study aims to determine the temperature and drying time of the study of the process of making tea from aloe vera skin. This study used a completely randomized design (CRD) consisting of two factors, namely the first factor is drying temperature (S), S1 : 50oC, S2: 60oC, S3: 70oC, S4: 80oC, and the second factor is drying time (L), L1: 2 hours, L2: 3 hours, L3: 4 hours, L4: 5 hours. Based on the results of the study, the best treatment was the water content of S4L4: 2.90%, and the yield of S1L1: 6.24%.